The View Beyond Looking: Isaac Julien’s Frantz Fanon: Black Skin, White Mask - Biko Agozino (Karib)
This paper is a simulation of a court hearing in which Frantz Fanon is accused of different things by different authors while I attempt to present a case for the defence of Fanon, indicating that a careful reading of his work will show that he has no case to answer. The paper arose from a plenary talk that I presented at a conference on immigrants in Europe which included the premier of the film on Fanon directed by Isaac Julien. The paper has been updated to reflect some current debates since the original presentation.